The Cambridge introduction to Ezra Pound - Nadel, Ira Bruce (Cambridge University, 2013)
zra Pound is one of the most visible and influential poets of the twentieth century. He is also one of the most complex, his poetry containing historical and mythical allusions, experiments of form and style and often controversial political views. Yet Pound's life and work continue to fascinate. This Introduction is designed to help students reading Pound for the first time. Pound scholar Ira B.